Hubungan Antara Kepuasan Kerja dengan Komitmen Organisasi Guru di Sekolah Dasar Negeri Se-Kecamatan Duren Sawit - Cantari, Ayunda Astha; Fuad, Nurhattati; Santoso, Heru (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2016)
This study aims to determine the relationship between job satisfaction and teacher’s organizational commitment of Elementary School in Kecamatan Duren Sawit. The method used is descriptive in the form of a survey. Samples were taken by using simple random sampling technique. Based on this technique, the sample size used in this study were 88 teachers from 760 teachers. Data collection for job satisfaction (X) and organizational commitment (Y) using a questionnaire. Data analysis techniques are used to test the hypothesis is to use a product moment correlation, with the prerequisite first tested the normality test, significance test and regression linearity. From the results of hypothesis testing to test the significance of the correlation is obtained that tcount > ttable as well as tcount = 3,121 and ttable = 1,988. Thus it can be said that the hypothesis can be accepted. This means that the null hypothesis (H0) is rejected. The results of this study it can be concluded that there is a positive relationship between job satisfaction with teacher’s organizational commitment of Elementary School in Kecamatan Duren Sawit.